Downsizing the physician workforce. - McClendon, B J (1997)
OBJECTIVE: To estimate the need for downsizing the physician workforce in a changing health care environment. METHODS: First assuming that 1993 physician-to-population ratios would be maintained, the authors derived downsizing estimates by determining the annual growth in the supply of specialists necessary to maintain these ratios (sum of losses from death and retirement plus increase necessary to parallel population growth) and compared them with an estimate of the number of new physicians being produced (average annual number of board certificates issued between 1990 and 1994). Then, assuming that workforce needs would change in a system increasingly dominated by managed care, the authors estimated specialty-specific downsizing needs for a managed care dominated environment using data from several sources. RESULTS: To maintain the 1993 199.6 active physicians per 100,000 population ratio, 14,644 new physicians would be needed each year. Given that an average of 20,655 physicians were certified each year between 1990 and 1994, at least 6011 fewer new physicians were needed annually to maintain 1993 levels. To maintain the 132.2 ratio of active non-primary care physicians per 100,000 population, the system needed to produce 9698 non-primary care physicians per year, because an average of 14,527 new non-primary care physicians entered the workforce between 1990 and 1994, downsizing by 4829, or 33%, was needed. To maintain the 66.8 active primary care physicians per 100,000 population ratio, 4946 new primary care physicians were needed per year, since primary care averaged 6128 new certifications per year, a downsizing of 1182, or 20% was indicated. Only family practice, neurosurgery, otolaryngology, and urology did not require downsizing. Seventeen medical and hospital-based specialties, including 7 of 10 internal medicine subspecialties, needed downsizing by at least 40%. Less downsizing in general was needed in the surgical specialties and in psychiatry. A managed care dominated-system would call for greater downsizing in most of the non-primary care specialties. CONCLUSION: These data support the need for downsizing the nation's physician supply, especially in the internal medicine subspecialties and hospital support specialties and to a lesser extent among surgeons and primary care physicians.